POTENTIAL OF HERBAL PLANTS AS ANTIHYPERTENSIVE THERAPY: A REVIEW - Merisa Restiani Arma; Maya Erisna; Sri Sumarni (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Hypertension has become a significant health problem in the world which the sufferer increases every year. Herbal treatment for lowering blood pressure that has been widely used in many countries shows the potential as an anti-hypertensive. This study aims to provide an overview of the herbs that have the effect of lowering blood pressures as the treatment of hypertension.Methods: This study used a systematic review based on the PRISMA (Preferred Reporting Items for Systematic Reviews & Meta-Analyses) protocol as a writing guideline. Electronic databases used in this study were Science Direct, PubMed, and Google Scholar. Only articles using interventions research design and containing full text both in English and Indonesian language were included in this study.Results: Of 207 articles recorded in the searching literature, only fourteen articles were included in this study. Study found that herbs which had the effect as antihypertensive therapy were Apium graviolens, Allium sativum, Centella asiatica, Orthosiphon stamineus benth, Beta vulgaris, and Vitis vinifera. The main components of those herbs consisted of n-butylphthalide, apigenin, potassium, flavonoids, triterpenoid, polysulfide, sinensetin, nitrate, and polyphenols. Conclusions: Many herbal plants found potentially lowering the blood pressures and considered as complementary treatment without any side effects. Further research is still needed on the effects of herbs in lowering the blood pressure to the human subject and its reversible effects, as well as the safety of herbs to human health when it is used for a long time.